Discussion of “The Consequences of Audit‐Related Earnings Revisions” - Hillison, Sean M.; Peecher, Mark E. (Contemporary Accounting Research, 2017)
Abstract We organize our discussion of Haislip, Myers, Scholz, and Seidel (2017) (hereafter HMSS ) around three areas: managing auditor business risk, a lack of auditor competence as an alternative story to auditors acting independently for their results, and drawing inferences from archival vis‐à‐vis experimental studies. We conclude our discussion by arguing that the investigation by HMSS sets the stage for future research concerning why earnings revisions occur and why auditors and CFO s appear to bear adverse consequences when they do occur.